Lanthanide Complexes (GdIII and EuIII) Based on a DOTA‐TEMPO Platform for Redox Monitoring via Relaxivity. Issue 17 (28th July 2022) - Barré, Richard; Mouchel dit Leguerrier, Damien; Ruet, Quentin; Fedele, Lionel; Imbert, Daniel; Martel‐Frachet, Véronique; Fries, Pascal H.; Molloy, Jennifer K.; Thomas, Fabrice
Abstract: Three lanthanide complexes (Ln=Gd, Eu) based on a DO3 A ([Ln(L1 )] ) or DO2 A ([Ln(L2–3 )] + ) platform appended by a redox active TEMPO‐based arm were prepared. Complex [Ln(L2 )] + shows an alkyne arm, offering the possibility of postfunctionalization by click reaction to yield [Ln(L3 )] + . The complexes demonstrate a redox response whereby the hydroxylamine, nitroxide and oxoammonium forms of the arm can be obtained in turn. Luminescence measurements on the europium complexes support an octadentate (L1, L3 ) or heptadentate (L2 ) chelation by the ligand, with one water molecule in the inner coordination sphere. The relaxivity was determined from 20 kHz to 30 MHz by fast‐field cycling NMR. The three Gd III complexes under their hydroxylamine form [Gd(L1 )] and [Gd(L2–3 )] + show r1 values of 7.0, 5.1 and 5.0 mM −1  s −1 (30 KHz), which increase to 8.8, 5.5 and 6.1 mM −1  s −1 in the nitroxide form. The radical complexes are not toxic against M21 cell lines, at least up to 40 μM. By using EPR spectroscopy we establish that they do not penetrate the cells with the exception of [Eu(L2 )] + . Abstract : The reported gadolinium complexes feature one coordinated water molecule, and the relaxivity increases upon oxidation of the hydroxylamine form of the TEMPO unit into the corresponding nitroxide radical.